Hydrotalcites and hydrated Mg-carbonates as carbon sinks in serpentinite mineral wastes from the Woodsreef chrysotile mine, New South Wales, Australia: Controls on carbonate mineralogy and efficiency of CO2 air capture in mine tailings. (December 2018) - Turvey, Connor C.; Wilson, Siobhan A.; Hamilton, Jessica L.; Tait, Alastair W.; McCutcheon, Jenine; Beinlich, Andreas; Fallon, Stewart J.; Dipple, Gregory M.; Southam, Gordon
Highlights: XRD, SEM and C isotope data were used to investigate carbonate mineral and hydrotalcite formation within mine tailings. CO2 availability controls carbonate with depth in the tailings at Woodsreef. Pyroaurite and coalingite are sequestering atmospheric CO2 at the Woodsreef chrysotile mine. Isotope fractionation in hydrotalcites depends on carbon availability. Detailed carbon accounting requires quantitative XRD and elemental C analysis. Abstract: Carbon mineralisation of ultramafic mine tailings can reduce net emissions of anthropogenic carbon dioxide by reacting Mg-silicate and hydroxide minerals with atmospheric CO2 to produce carbonate minerals. We investigate the controls on carbonate mineral formation at the derelict Woodsreef chrysotile mine (New South Wales, Australia). Quantitative XRD was used to understand how mineralogy changes with depth into the tailings pile, and shows that hydromagnesite [Mg5 (CO3 )4 (OH)2 ·4H2 O], is present in shallow tailings material (<40 cm), while coalingite [Mg10 Fe 3+ 2 (CO3 )(OH)24 ·2H2 O] and pyroaurite [Mg6 Fe 3+ 2 (CO3 )(OH)16 ·4H2 O] are forming deeper in the tailings material. This indicates that there may be two geochemical environments within the upper ∼1 m of the tailings, with hydromagnesite forming within the shallow tailings via carbonation of brucite in CO2 -rich conditions, and pyroaurite and coalingite forming under more carbon limited conditions at depth. Radiogenic isotope results indicate hydromagnesite and pyroaurite have a modern (F 14 C > 0.8) atmospheric CO2 source. Laboratory-based anion exchange experiments, conducted to explore stable C isotope fractionation in pyroaurite, shows that pyroaurite δ 13 C values change with carbon availability, and 13 C-depleted signatures are typical of hydrotalcites in C-limited environments, such as the deep tailings at Woodsreef. Quantitative XRD and elemental C data estimates that Woodsreef absorbs between of 229.0–405.1 g CO2 m −2 y −1 .